CXCR4 prevents dispersion of granule neuron precursors in the adult dentate gyrus. Issue 12 (10th September 2013) - Schultheiß, Clara; Abe, Philipp; Hoffmann, Frauke; Mueller, Wiebke; Kreuder, Anna‐Elisabeth; Schütz, Dagmar; Haege, Sammy; Redecker, Christoph; Keiner, Silke; Kannan, Suresh; Claasen, Jan‐Hendrik; Pfrieger, Frank W.; et al.
<x xml:space="preserve">Abstract</x> Neurogenesis in the adult dentate gyrus (DG) generates new granule neurons that differentiate in the inner one‐third of the granule cell layer (GCL). The migrating precursors of these neurons arise from neural stem cells (NSCs) in the subgranular zone (SGZ). Although it is established that pathological conditions, including epilepsy and stroke, cause dispersion of granule neuron precursors, little is known about the factors that regulate their normal placement. Based on the high expression of the chemokine CXCL12 in the adult GCL and its role in guiding neuronal migration in development, we addressed the function of the CXCL12 receptor CXCR4 in adult neurogenesis. Using transgenic reporter mice, we detected Cxcr4‐GFP expression in NSCs, neuronal‐committed progenitors, and immature neurons of adult and aged mice. Analyses of hippocampal NSC cultures and hippocampal tissue by immunoblot and immunohistochemistry provided evidence for CXCL12‐promoted phosphorylation/activation of CXCR4 receptors in NSCs in vivo and in vitro. Cxcr4 deletion in NSCs of the postnatal or mature DG using Cre technology reduced neurogenesis. Fifty days after Cxcr4 ablation in the mature DG, the SGZ showed a severe reduction of Sox2‐positive neural stem/early progenitor cells, NeuroD‐positive neuronal‐committed progenitors, and DCX‐positive immature neurons. Many immature neurons were ectopically placed in the hilus and inner molecular layer, and some developed an aberrant dendritic morphology. Only few misplaced cells survived permanently as ectopic neurons. Thus, CXCR4 signaling maintains the NSC pool in the DG and specifies the inner one‐third of the GCL as differentiation area for immature granule neurons. © 2013 Wiley Periodicals, Inc.